(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education is important to India’s ambitions to become a dominant player in global information economy. The paper correlates the growth of education system in India to a changing various levels of education policy ways of ensuring that education stays affordable and accessible to everyone. Another of the prevailing problems of the education system in its present existence is the quality of education the quality of education aims to be a focus of prosperity. For a person to prosper in the society, education is considered imperative. The main objective of this paper is to explain the Indian education system, changes to the Indian education system reorganization of education at various levels for enhancing the Indian education system.